Nurses' Perceptions of Caring-Based Holistic Nursing Care in Hospitals: A Qualitative Study - Heryyanoor Heryyanoor; Diana Hardiyanti; Melinda Restu Pertiwi (SEHATI: Jurnal Kesehatan, 2025)
Hospital nurses have not optimally implemented holistic nursing care with a caring approach, which can affect the quality of service and patient satisfaction levels. Research has explored nurses' perceptions of implementing holistic nursing care based on hospital care. Qualitative research was designed using a phenomenological approach. Twelve nurse participants cared for patients with degenerative diseases. Data were collected through in-depth interviews and analyzed thematically. The ethics commission at Stikes Intan Martapura approved the study, and participants also gave written consent. The study identified five main themes, including understanding the concept of holistic care, its impact on patient satisfaction and loyalty, experiences of providing and receiving care, essential components of care, and how to implement it in clinical practice. The findings indicated that effective therapeutic communication, caring attitudes, professional ethics, and institutional support were key factors in the success of holistic nursing care. This study emphasized the importance of a multidimensional approach that includes biological, psychological, social, spiritual, and economic aspects in nursing practice. This study contributes to understanding caring-based holistic nursing care by highlighting its essential components and positive impact on patient satisfaction and loyalty. The findings provide insights to improve nursing practice and institutional support systems. Further studies are recommended to develop intervention strategies to address the challenges and measure patient outcomes quantitatively to advance holistic nursing care in the clinical setting.